1995
DOI: 10.1177/028418519503600418
|View full text |Cite
|
Sign up to set email alerts
|

MR Imaging and Radiography of Patients with Cervical Hyperextension—Flexion Injuries after Car Accidents

Abstract: Fifty-two patients underwent MR imaging and conventional radiography of the neck within 4 days after a hyperextension-flexion injury. The patients also had follow-up investigations during the first 2 years. The images did not reveal any serious lesions in any of them. Based on the main MR and radiographical findings the patients were divided into 4 groups; no findings, posture abnormalities, spondylosis and disc pathology (from MR images) or reduced intervertebral space (from the radiographs). The outcomes of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
2

Year Published

1998
1998
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 13 publications
1
16
0
2
Order By: Relevance
“…[55][56][57][58][59] MRI has also failed to correlate consistently with the frequency and severity of whiplash injury symptoms and outcome. 55,60 It has been suggested that preexisting neck pain plays an important part in the etiology of whiplash injury. 61 Neck pain also occurs in the general population as a result of causes unrelated to trauma.…”
Section: Discussionmentioning
confidence: 99%
“…[55][56][57][58][59] MRI has also failed to correlate consistently with the frequency and severity of whiplash injury symptoms and outcome. 55,60 It has been suggested that preexisting neck pain plays an important part in the etiology of whiplash injury. 61 Neck pain also occurs in the general population as a result of causes unrelated to trauma.…”
Section: Discussionmentioning
confidence: 99%
“…There is until now no convincing evidence of a specific neck injury that can be expected to commonly cause chronic damage in the neck and continue to generate chronic pain or other chronic symptoms of the late whiplash syndrome 1422 25 26 Notwithstanding these observations, given that in Lithuania, Greece, and Germany the acute whiplash injury commonly occurs with pain resolving within 6 weeks, the exact pathology of most acute whiplash injuries may be largely irrelevant. From engineering studies, radiological studies, and traumatological principles, the acute injury is in most cases a muscle or ligament sprain 14…”
Section: The Need For a Biopsychosocial Modelmentioning
confidence: 99%
“…16 Yet, as we have reviewed, controlled studies of now more than 1000 whiplash patients reporting chronic symptoms have routinely failed to demonstrate such injuries (G Borchgrevink, et al Third Scientific Meeting of the Society of Magnetic Resonance, Nice, France, 1995) 1416 18 19 In the vast majority of whiplash claimants, radiological findings, whether by radiography or magnetic resonance imaging, are not helpful in demonstrating the injury or source of symptom reporting. Their role is only to exclude a fracture or to locate the source of a clinically evident neurological abnormality.…”
Section: A Modelmentioning
confidence: 99%